Sustainability Status Assessment of Urban Agriculture Types in Malang City - Intan Ratri Prasundari; Setyo Tri Wahyudi; Anthon Efani; Reny Tiarantika (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
Urban agriculture (UA) and urban-peri-urban agriculture (UPA), is one of the approaches to improve sustainability of urban food system. Urban agriculture can increase access to fresh food for the community, by shortening the food supply chain. There are many impacts from ecological, economic, social dimensions. However, it is undeniable that urban agriculture also brings other negative impacts in various dimensions. Which directly or indirectly affect the sustainability of urban agriculture. Many urban agriculture have low sustainability. Malang City itself has the potential for urban agriculture. At least there are 7 types of urban agriculture in Malang City, namely (1) wetland/irrigated agricultural land, (2) Rainfed dryland farming, (3)recreational activity, (4) community gardening, (5) commercial farming, (6) agro-educational tourism, (7) institution. The purpose of this study is to assess the sustainability status of each type of urban agriculture. A quantitative approach, using the multidimentional scaling method and RAPHYTON tools was used to analyze the data. Primary data were collected from expert informant interviews, supporting informants, field surveys and observations. The results of the analysis showed that the sustainability level of urban agriculture various types in Malang City is generally in the moderately sustainable category. The ecological dimension of irrigated agricultural land is categorized as unsustainable. Conversely, the highest sustainability status (categorized as sustainable) is achieved by agro-educational tourism type agriculture in the social dimension. This research also suggests attributes that leverage the sustainability status of each dimension. One of them is the application of integrated agriculture to achieve ecological sustainability.